Fluctuations of Independence in the Letter of Viscardo and Gusmán (Anclajes, 2019)
In Letter to the Spanish Americans, Juan Pablo Viscardo y Gusmán understands Independence as a renunciation of a covenant and as emancipation of a guardianship. The fluctuation between both interpretations corresponds to the reference to two traditions –Spanish Neo-Scholasticism and Enlightenment thought–, but also to two different narratives of independence itself.
Keywords: Viscardo y Guzmán; Independence; emancipation; creole; Illustration